Peran Hakim dalam Penemuan Hukum Pidana Progresif: Perspektif Sociological Jurisprudence - Zurnetti, Aria; Raihany, Farras Audia (Nagari Law Review, 2025)
Judges' legal findings play a role in filling legal gaps and realizing justice that is adaptive to social dynamics. Sociological jurisprudence emphasizes that law must consider the values that live in society. This study examines the concept and implementation of this approach in progressive criminal law in Indonesia. Using the juridical-normative method through literature study, it was found that judges can interpret the law to achieve substantive justice. Applying this approach makes decisions more responsive to social reality, as reflected in various progressive decisions that accommodate living law. However, its implementation faces challenges related to the principle of legality and the prohibition on analogy in criminal law. Therefore, a balance is needed between legal certainty and flexibility in legal findings to make the justice system fairer.